Early Childhood Teachers' Psychological Well-Being: Exploring Potential Predictors of Depression, Stress, and Emotional Exhaustion - Jeon, Lieny; Buettner, Cynthia K.; Grant, Ashley A. (Early education and development, 2018)
Research Findings: Early childhood teachers' psychological well-being influences the nurturing and learning classroom climate in early care and education as well as children's development. However, less is known about predictors of teachers' psychological well-being in preschool. The purpose of this study was to explore associations between potential predictors of teachers' psychological well-being-such as professional background, teaching efficacy, and work environment-and teachers' self-perceived depression, stress, and emotional exhaustion after controlling for individual demographics. A total of 1,129 teachers serving preschool-age children (3- and 4-year-olds) in the United States participated in the study. Teachers responded to a questionnaire asking about their background, work environment, and social-emotional attributes. Multiple regression analysis revealed that levels of teachers' self-efficacy and work environments are generally associated with their psychological well-being above and beyond their personal and professional backgrounds. Practice or Policy: The results of this study suggest that it is important to help teachers build teaching competence and efficacy and to prepare them to handle stressors from work environments in order to reduce their psychological burden. In addition, we suggest that positive work climates need to be created for teachers and children at the program level.